Expanding student nurse placement activity in Welsh care homes: An evaluation study - Sharon Williams (International Journal of Nursing Practice, 2024)
Aim: Expanding and sustaining student nurse placements outside of the acute sector is a universal challenge. This paper aims to evaluate the Care Home Education Facilitator Role introduced in one area of Wales, United Kingdom, and to report on the outcomes achieved from this novel role. Methods: Semi-structured interviews were undertaken with key stakeholders including the Care Home Education Facilitator postholder leading the pilot, care home managers, higher education institutions' placement managers/coordinators, student nurses and national health service staff. Results: Five key areas were identified, which included timing of introducing the post and establishing a clear rationale and understanding of the intention of the role. The benefits, challenges and suggested improvements to the Care Home Education Facilitator initiative are provided. Conclusion: Introducing the role of the Care Home Education Facilitator to work closely with key stakeholders resulted in increased placements for student nurses, but investing time in developing relationships with these stakeholders was critical to the success of the role.